إدارة الوقت وأثرھا على ضغوط العمل لدى مدیري المدارس الثانویة بمدینتي طرابلس وبنغازي - Gamel A. Kherallh Maayouf (Universiti Sains Islam Malaysia, 2024)
The study seeks to discuss the issue of time management and its impact on job stress among secondary schools’ principals (Schools’ Headmasters) in Tripoli and Benghazi. The objectives of the study briefed on the following points: – To identify the level of time management practices among the secondary schools’ principals (Schools’ Headmasters) in Tripoli and Benghazi. And To uncover the level of work stress faced by secondary schools’ principals (Schools’ Headmasters) in Tripoli and Benghazi. And To identify the impact of time management on work stress of secondary schools (Schools’ Head asters), in Tripoli and Benghazi. And To find out if there is statistically any significant differences between the variables related to the principal (Headmaster), based on (sex, educational qualification, years of experience) and the level of managing their time management. And To examine if there is statistically any significant differences between the variables related to the principal (Headmaster), (sex, educational qualification, years of experience) and the level workplace stress which they are exposed to. Since the study focuses on demonstrating the impact of time management pertaining workplace stress on secondary schools’ principals (Schools’ Headmasters), as well as, its based on analytical descriptive study via the questionnaire method, the researcher believes that applying the aforesaid method is an appropriate tool in conducting such studies, therefore, the researcher develops a questionnaire form consisting of (54) items covering the said studies aspects namely (time management, workplace stress). The questionnaires have been distributed to (202) principals as participants, after approving and confirming the validity and reliability of the said questionnaire, the researcher used SPSS program to analysis his data statistically, which resulted into to several findings including the following:- Low level of time management practices among the secondary school principals (Schools’ Headmasters). And High level of workplace stress among secondary schools’ principals (Headmasters). And Time management has negative impact on workplace stress among secondary schools’ principals (Headmasters). The study also recommends the need of providing training to the Headmasters during the tenure of their office, in form of practical workshops about the efficiency of time management and its relationship to workplace stress on secondary schools’ principals (Headmasters), as well as the importance of upgrading the management systems in schools, so as to give the of secondary schools’ principals ( Headmasters) the necessary power that enables them to create an excellent environment of workplace, aiming at eradicating or reducing the suffering of stress at workplace.